ANALYZE FACTORS DETERMINANT OF TOTAL CREDIT RECEIVED ON THE DEBITORS OF BANK PERKREDITAN RAKYAT IN SURAKARTA - Edi Wibowo, Dorothea Ririn Indriastuti & (PROCEEDING INTERNASIONAL SEMINAR, 2015)
This study aims to analyze the influence of profitability, collateral, and the long business to total credit received on the debitors. This study use sample of debtors who took the General Loan (Kredit Umum) of Bank Prekreditan Rakyat (BPR) in Surakarta the respondents were 62 debtors. Data collection techniques using documentary techniques. While the technique of data analysis using multiple linear regression analysis, t test, F test and determination coefficient test.Based on the results of data analysis: (1) Profitability, collateral, and long business in individually have a positive and significant effect on the total credit received on the debtors of BPR in Surakarta, then hypothesis 1 was confirmed. (2) Profitability, collateral, and long operating in simultaneously have a positive and significant effect on the total credit received on the debitors of BPR in Surakarta, then hypothesis 2 was confirmed. (3) In this study, indicate that profitability variable was the most dominant influence to the total credit received on the debtors, then hypothesis 3 was confirmed. (4) Results of determination coefficient test is R2 = 0.620; it means that the profitability, collateral, and long business are explain is 62% while the rest 38% influenced by other variables outside the model that is not investigated such as current capital or demographic factors like age and education level.Based on this research for the debtors are advised to increase the value profitability so as to obtain an opportunity to obtain a larger loan amount. To improve profitability, in addition to increasing sales is expected employers to manage costs efficiently. In deciding the bank credit, especially in this case the BPR in Surakarta to continue to apply prudential banking principles with the aim of effectively controlling the occurrence of bad credit problems.Key word : profitability, collateral, long business, total credit, debitor